Radiation Exposure From Pediatric CT Scans and Subsequent Cancer Risk in the Netherlands. (18th July 2018) - Meulepas, Johanna M; Ronckers, Cécile M; Smets, Anne M J B; Nievelstein, Rutger A J; Gradowska, Patrycja; Lee, Choonsik; Jahnen, Andreas; van Straten, Marcel; de Wit, Marie-Claire Y; Zonnenberg, Bernard; Klein, Willemijn M; Merks, Johannes H; et al.
Abstract: Background: Computed tomography (CT), a strong diagnostic tool, delivers higher radiation doses than most imaging modalities. As CT use has increased rapidly, radiation protection is important, particularly among children. We evaluate leukemia and brain tumor risk following exposure to low-dose ionizing radiation from CT scans in childhood. Methods: For a nationwide retrospective cohort of 168 394 children who received one or more CT scans in a Dutch hospital between 1979 and 2012 who were younger than age 18 years, we obtained cancer incidence, vital status, and confounder information by record linkage with external registries. Standardized incidence ratios were calculated using cancer incidence rates from the general Dutch population. Excess relative risks (ERRs) per 100 mGy organ dose were calculated with Poisson regression. All statistical tests were two-sided. Results: Standardized incidence ratios were elevated for all cancer sites. Mean cumulative bone marrow doses were 9.5 mGy at the end of follow-up, and leukemia risk (excluding myelodysplastic syndrome) was not associated with cumulative bone marrow dose (44 cases). Cumulative brain dose was on average 38.5 mGy and was statistically significantly associated with risk for malignant and nonmalignant brain tumors combined (ERR/100 mGy: 0.86, 95% confidence interval = 0.20 to 2.22, P = .002, 84 cases). Excluding tuberous sclerosis complex patients did not substantially change the risk. Conclusions: We found evidence that CT-related radiation exposure increases brain tumor risk. No association was observed for leukemia. Compared with the general population, incidence of brain tumors was higher in the cohort of children with CT scans, requiring cautious interpretation of the findings.